A dynamical origin for planets in triple star systems. Issue 1 (27th November 2018) - Fragione, Giacomo; Loeb, Abraham; Ginsburg, Idan
ABSTRACT: Recent radial velocity and transit data discovered ∼100 planets in binary or triple stellar systems out of the entire population of a few thousand known planets. Stellar companions are expected to strongly influence both the formation and the dynamical evolution of planets in multiple star systems. Here, we explore the possibility that planets in triples are formed as a consequence of the dynamical interactions of binaries in star clusters. Our simulations show that the probability of forming a planet-hosting triple as a consequence of a single binary–binary scattering is in the range0.5-3 per cent, when one of the binaries hosts a planet. Along with other formation scenarios, binary–binary encounters are a viable way of creating planet-hosting triple systems. The recently launched TESS satellite is expected to find a larger sample of planets in triple systems, and to shed light on their origin.